Degradabilidade ruminal do amido de silagem de milho, farelo de soja e sorgo grão, em bovinos da raça Nelore - Rossi Júnior, Paulo (1997)
Four Bos indicus (Nellore) ruminally-fistulated animals, averaging 36 months of age and 520 kg, were used in a randomized block design to study the ruminal degradability of starch in corn silage, soybean meal, and sorghum grain. The experimental diets consisted of two levels of concentrate (18 and 39%) plus corn silage. The concentrate ingredients used were soybean meal, cottonseed meal, corn grain, and sorghum grain. The degradation rate of sorghum grain increased 40.2% in diet 2 . The potential degradability of starch (PDS) was similar in the two diets. There was no difference between the two diets in the effective degradability of starch (EDS) in corn silage. There was a significant increase of 26.5% in the EDS of starch in sorghum grain with the increase of level of concentrate in the diet, and considering the lag time in the calculation. The starch level estimated in this study was lower than the values cited in the literature, probably due to different laboratory methods for determining the starch content in feedstuffs. Previous studies suggested using a minimum of 6 incubation intervals between 2 and 24 hours.